2022
DOI: 10.4102/sajip.v48i0.1902
|View full text |Cite
|
Sign up to set email alerts
|

A diary study of the impression management strategies utilised by industrial and organisational psychology interns

Abstract: Orientation: When interns enter a new workplace, they are compelled to create and maintain a good impression through a range of image-enhancing behaviours. Impression management strategies can help interns to do this.Research purpose: This study aimed to understand the strategies used by industrial and organisational (I/O) psychology interns, their goals for using them and the targets of these strategies.Motivation for the study: Interns are generally new to the workplace and, as such, may not be aware of how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Furthermore, it would be interesting to address the emotional consequences of the use of exemplification tactics on co-workers. In this sense, it has been noted that self-sacrifice behaviors tactics “may make others around them feel inadequate and guilty” (McGowan & Sekaja, 2022 , p. 7). Moreover, recent studies have found that some IM tactics (i.e., self-promotion and ingratiation) moderate the influence of person-organization fit on perceived workplace inclusion (Chen & Tang, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it would be interesting to address the emotional consequences of the use of exemplification tactics on co-workers. In this sense, it has been noted that self-sacrifice behaviors tactics “may make others around them feel inadequate and guilty” (McGowan & Sekaja, 2022 , p. 7). Moreover, recent studies have found that some IM tactics (i.e., self-promotion and ingratiation) moderate the influence of person-organization fit on perceived workplace inclusion (Chen & Tang, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such a survival-centred mode becomes crucial, especially given some noted challenges experienced by interns in the world of work (McHugh 2017). In addition, interns usually do not have the necessary social capital and networks to be able to survive within the world of work (McGowan & Sekaja 2022). In essence, their survival within the world of work could be linked to seeking such social capital and networks.…”
Section: Empirical Literature Reviewmentioning
confidence: 99%
“…Other empirical investigations concentrated on the effect, impact, and influence of impression management on other criterion variables other than employee contextual performance [28,29]. Again, just recently, McGowan & Sekaja [30] and Delport et al [31] examined the effect of impression management tactics on other variables that are different from employee contextual performance. This has created a lacuna in impression management research.…”
Section: Impression Management and Employee Contextual Performance Inmentioning
confidence: 99%
“…Kandpal & Chaubey [29] investigated the impression management tactics used by staff in selected higher institutions located in Uttarakhand, India, and found that most senior staff employ selfpromotion and, ingratiation to impress their counterparts in the organizations. McGowan & Sekaja [30] identified the impression management strategies used by organizational psychology interns in South African firms and, found that they employ ingratiation, exemplification, self-promotion, rendering favours, professionalism, conformity, openness to learning, and strategic relationship building. Delport et al [31] explored the impression management tactics of Afrikaans coloured managers in South Africa and discovered that coloured Afrikaans managers used different impression management tactics to influence their subordinates.…”
Section: -3-impression Management and Employee Contextual Performancementioning
confidence: 99%